Políticas gubernamentales para una colaboración tecnológica inter-firmas en MERCOSUR - Alcorta, Ludovico (2000)
This paper examines sorne of the experiences in information and knowledge sharing involving MERCOSUR firms and the role of government in ensuring their success. The analysis of technological collaborations suggested that the better prepared a corporation entered an agreement the more successful it was likely to be. lt also pointed out that where interactions were intense, well intended and transparent; included personnel exchange; were properly assessed; and, involved receptive participants, learning progressed smoothly and partners were satisfied. Benefits of the collaborations included new patentable and non patentable products and new factories as well as building trust between partners. Governments can facilitate collaborations by providing a sound economic and political environment and consistent macro and sectoral policies. Government policies can help initiating and sustaining technological partnerships by becoming an alternative source of information and knowledge and a forum for information exchange and discussion, by promoting and funding research and development projects, by brokering and delimiting responsibilities between potential partners and by providing markets. Finally, governments can assist in the success of technological collaborations by involving business associations and other relevant institutions.